(untitled) (Medical Forum Monthly, 2021)
Objective: To determine the nature of complications in dengue fever in Khyber Pakhtunkhwa province. Study Design: Descriptive study. Place and Duration of Study: This study was conducted at two major tertiary care hospitals of Khyber Pakhtunkhwa from July 2020 to November 2020. Material and Methods: Demographics, clinical features and laboratory findings were recorded on pre-designed Performa. Results: Conditions complicating dengue fever included Hepatitis (26.3%), Pneumonia (15.7%),Dengue Hemorrhagic Fever(15.7%).Pleural effusion(10.5%),Multi-organ Failure(10.5%),Renal failure(7.8%),Dengue Shock Syndrome(5.2%),Encephalopathy(2.6%) and Myocarditis(2.6%). Conclusion: Early diagnosis and treatment is important in order to avoid complications in dengue fever.